Involvement of anomalously As-Au-rich fluids in the mineralization of the Heilan'gou gold deposit, Jiaodong, China: Evidence from trace element mapping and in-situ sulfur isotope composition. (July 2018) - Feng, Kai; Fan, Hong-Rui; Hu, Fang-Fang; Yang, Kui-Feng; Liu, Xuan; Shangguan, Yi-Ning; Cai, Ya-Chun; Jiang, Peng
Highlights: Pyrite crystals with Au- and As-rich rims are identified in the Heilan'gou deposit. Anomalously As-Au-rich fluids were incorporated into the ore-forming system during the late ore-forming stage. Arsenic may play an important role for the formation of ultra-high grade gold ores. Abstract: The Mesozoic (∼120 Ma) Heilan'gou gold deposit, located in the Jiaodong gold province, eastern margin of the North China Craton (NCC), consists of several ultra-high grade (up to 600 g/t) auriferous quartz veins in the early Cretaceous Guojialing granodioritic pluton. Ore-related pyrite crystals from this deposit show complex textures. In this study, EMP, Nano-SIMS trace element mapping and in-situ sulfur isotope analyses were conducted to characterize the textural and compositional features. Two types of pyrite were identified. Type I crystals (Py-I), hosted in gold-quartz-pyrite veins, are generally homogeneous in chemical composition. They contain low concentrations of As (<0.2 wt.%) and Au (<0.06 wt.%), and have δ 34 S values ranging from 6.6‰ to 7.9‰. Minor amounts of visible gold grains were observed in fractures of Py-I. Type II pyrite crystals (Py-II), hosted in gold-polymetallic sulfide veins, are commonly composed of an As-poor core (Py-IIa) and an As-rich rim (Py-IIb), with clear boundaries between the two domains. Py-IIb grains normally show oscillatory or patchy zonings of arsenic, and are spatially associated with visible gold and As-Te-Ag-Cu-Pb mineral inclusions. The Py-IIa shows geochemical signatures similar to Py-I, whereas, Py-IIb contains relatively high concentrations of As (0.4–2.5 wt.%, 1.47 wt.% on average) and Au (0.1 wt.% on average), and elevated δ 34 S values (8.1–8.8‰). Based on the distinctive textural and compositional signatures between Py-IIa and Py-IIb, it is proposed that anomalously As-Au-rich fluids were injected into hydrothermal systems during the late ore-forming stage, which may have intensively interacted with certain sedimentary rocks. The involvement of these fluids, firstly documented in this study, can largely explain the occurrence of native gold ore shoots at Heilan'gou. In addition, the intimate association between As and Au highlights the important roles of As in enrichment of Au in the Jiaodong gold district.